To Investigate the Relationship between CSR of Companies and Their Market Valuation (Equity Valuation): Northern India: The impact of CSR on company market value: A case study of Northern India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Corporate Social Responsibility (CSR) has been widely studied in the past with little success on direct impact on firm’s valuation. The following research investigates the relationship between CSR of companies and their market value a case study of 20 large size companies in Northern India that are listed in National Securities Exchange (NSE). The research uses secondary data for primary analysis and applies MS Excel to analyze data. The data was collected from annual company reports and NSE website for the past 5 years. The research used CSR spending and market cap to investigate the relationship in CSR of companies and market value. The research found that CSR spending and stock valuation is positively related. The concluded that firm valuation can be increased by increasing CSR activities. The research recommends that all companies should adopt a CSR in order to increase the company market value.